Pengaruh Ukuran Partikel Biochar dalam Media Irigasi Kapiler dan Ketinggian Lubang Tanam yang Berbeda dalam Sistem Vertikultur terhadap Pertumbuhan dan Hasil Selada (Lactuca Sativa L.) di Lahan Kering - Buatefa, Bartholomeus Aryanto; Neonbeni, Eduardus Yosef; Bria, Deseriana; Ndua, Natalia Desy Djata (Fakultas Pertanian, Sains, dan Kesehatan, Universitas Timor, 2024)
This study aims to test the size of biochar particles in capillary irrigation media and the height of planting holes in a vertical culture system on the growth and yield of lettuce (Lactuca sativa L.) in dry land using the Split Plot Design (RPT) factorial method with 3 replications. The first factor is the size of biochar particles consisting of three levels, namely: unsieved biochar, finely sieved biochar <0.5 mm, and the remainder of the sieve> 0.5 mm. The second factor is the height of the vertical culture consisting of three levels, namely: 25 cm, 75 cm, 125 cm from the ground surface. The results showed that the treatment of biochar particle size in capillary irrigation media that was able to increase lettuce growth and production was finely sieved biochar <0.5 mm, namely in the observation of plant height at the age of 14 MST, 21 MST, 28 MST and the root crown ratio. The treatment of planting hole height in the vertical culture system that is able to increase lettuce growth and production is the treatment of planting hole height of 25 cm which gives the best results for plant height at the age of 21 MST, 28 MST and root crown ratio.